Design and evaluation of 4-DoF machine for improving muscle control and upper extremity rehabilitation - Wongwatcharanon, Thanyaporn; Kiatchaipar, Methasit; Pinupong, Chalearmpong; Kooncumchoo, Patcharee; Rungroungdouyboon, Bunyong (2023)
Poor upper limb movement control and coordination are major problems in patients with stroke. A novel combination of muscle and multi-joint movement increases mobility, allows for the degree of freedom in shoulder and elbow joint, and facilitate patients to learn and control their movement. The assisted movement with a symmetrical counterweight balance system and real-time feedback is proposed to enhance and facilitate the movement of paresis muscles. The power assist uses purely mechanical and assisted movement from the non-paretic arm. The feedback system receives data from a three-axis load cell sensor on both sides of the handlebar during movement and feedback force from both sides in real time. The display of real-time feedback is provided and enables subjects to adjust and correct their movement. Two combined movements were performed in five healthy subjects for testing the device system and correlation of force from the load cell and muscle activity from surface electromyography (sEMG). The results showed that the new upper limb rehabilitation machine with feedback and a symmetrical counterweight balance system can achieve mass balance in all positions. The device is robust, safe, and easy for the subject to move a combined movement of the shoulder joint and elbow joint. The force from the load cell sensor occurs simultaneously with muscle activation during movement. This system helps the patient to learn and control their force from the paretic limb. The high repetitions from practice with an accuracy of muscle force and movement control will enhance motor learning and facilitate motor recovery during the rehabilitation period.
Keywords: Muscles; Medical rehabilitation